Efficacy of Tamsulosin and Alfuzosin in Management of Distal Ureteral Stones - Piya, Bimochan; Bhattarai, Abhishek (Med Phoenix, 2021)
Introduction: Urinary tract calculi are the most frequent condition in urology clinics worldwide. The overall prevalence is about 5 % and lower urinary tract stones account for 70% among them. Medical expulsive therapy has been used to treat distal ureteric stone as it reduces symptoms and facilitates stone expulsion. The aim of this study is to evaluate and compare the efficacy of tamsulosin and alfuzosin as medical therapy in ureteric stones. Materials and Methods: A total of 87 patients with distal ureteral stones of size ≤10 mm were randomly divided into 3 groups. Group A patients (n-30) received 0.4 mg of tamsulosin daily, group B patients (n-29) received 10 mg of alfuzosin daily and group C patients (n-28) received 75 mg of diclofenac sodium. Patients in all groups received diclofenac sodium for one week and then as required. Follow-up was done on a weekly basis for 4 weeks. The stone expulsion rate, time for stone expulsion, and side-effects were recorded in each group. Results: The mean stone size (5.66, 5.79, 5.67) mm and age (29.1, 30.31, 29.4) were comparable in each group. The stone expulsion rate was 83.3%, 79.3%, and 50% in groups A, B, and C respectively. It showed that both the study groups (Group A and Group B) were effective than the control group (p-value 0.006 and 0.02 respectively) but there was no difference between tamsulosin and alfuzosin (p-value 0.69). The duration of stone expulsion was 11.5 days, 11.8 days, and 17.3 days for Group A, B, and C respectively. The drugs related side effects reported by patients were mild and transient. Conclusion: The use of tamsulosin and alfuzosin for the medical treatment of ureteric stones proved to be safe and effective and neither did have any significant benefits over the other.